Comparison of Ultrasound-Guided Transgluteal and Finger-Guided Transvaginal Pudendal Nerve Block Techniques: Which One is More Effective? - Kale, Ahmet (Int Neurourol J, 2019)
PURPOSE: Pudendal neuralgia (PN) is a painful and disabling condition, which reduces the quality of life as well. Pudendal nerve infiltrations are essential for the diagnosis and the management of PN. The purpose of this study was to compare the effectiveness of finger-guided transvaginal pudendal nerve infiltration (TV-PNI) technique and the ultrasound-guided transgluteal pudendal nerve infiltration (TG-PNI) technique. METHODS: Forty patients who underwent PNI for the diagnosis of PN were evaluated. Thirty-five of these 40 patients, who were diagnosed as PN, underwent a total of 70 further unilateral PNI. All the patients underwent PNI for twice after the first diagnostic PNI, 1 week apart. RESULTS: In the ultrasound (US)-guided TG-PNI group, the success rate was 68.8% (11 of 16) in both “pain in the sitting position” and “pain in the region from the anus to the clitoris.” The success rate of blocks in the US-guided TG-PNI group was 75% (12 of 16) in terms of pain during/after intercourse. In the finger-guided TV-PNI group, the success rate was 84.2% in both “pain in the sitting position” and “pain in the region from the anus to the clitoris.” The success rate of blocks in the fingerguided TV-PNI group was 89.5% (17 of 19) in terms of pain during/after intercourse. There was no statistically significant difference in the success rate of the 3 assessed conditions between the 2 groups (P>0.05). CONCLUSIONS: The TV-PNI may be an alternative to US-guidance technique as a safe, simple, effective approach in pudendal nerve blocks.